2014
DOI: 10.1017/jfm.2014.408
|View full text |Cite
|
Sign up to set email alerts
|

Drawing of micro-structured fibres: circular and non-circular tubes

Abstract: A general mathematical framework is presented for modelling the pulling of optical glass fibres in a draw tower. The only modelling assumption is that the fibres are slender; cross-sections along the fibre can have general shape, including the possibility of multiple holes or channels. A key result is to demonstrate how a so-called reduced time variable τ serves as a natural parameter in describing how an axial-stretching problem interacts with the evolution of a general surface-tension-driven transverse flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
119
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(122 citation statements)
references
References 40 publications
3
119
0
Order By: Relevance
“…It has also been shown that the description for capillary geometries [9] provides practical insights into the drawing of more complex multi-hole geometries [29]. Based, in addition, on an earlier leadingorder analysis for extensional flows in slender geometries [32], a mathematical leading-order framework of fiber drawing, specified to arbitrary cross-plane geometries, is applied in [33] and subsequent papers [34,35].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been shown that the description for capillary geometries [9] provides practical insights into the drawing of more complex multi-hole geometries [29]. Based, in addition, on an earlier leadingorder analysis for extensional flows in slender geometries [32], a mathematical leading-order framework of fiber drawing, specified to arbitrary cross-plane geometries, is applied in [33] and subsequent papers [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Of course, the approaches used in the drawing theory are adjusted, first of all, to arrive at a basic understanding of influencing factors of the technical fiber drawing process, such as peculiarities of drawing of fibers with complicated cross-sections (see, e.g., [33][34][35]). The limiting case of equal, impressed axial velocities on both sides of the heating zone (collapsing limit), if mentioned at all [9,26,33], is considered being of minor interest, e.g., for preform fabrication (see, e.g., [33]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our approach assumes the shape of the neck-down is slender, that is = √ S 0 /L 1, and this significantly simplifies the full three-dimensional Navier-Stokes equations. As outlined in detail in [3] and [4], we make various perturbation expansions in 2 and solve a coupled system of equations for the leading-order flow in the axial direction (that is, along the axis of the fibre) and for the flow in the cross-plane (in every cross-section along the length of the neck-down).…”
Section: Asymptotic Modelling Approachmentioning
confidence: 99%
“…The modelling approach of the present study has been developed by the authors [3], [4] (building on earlier work in [5]- [7], among others) specifically for the problem of fibre drawing. This approach immediately has an advantage over a package which is, by nature, designed to be as general as possible in scope and not context specific.…”
Section: Introductionmentioning
confidence: 99%